Problematic Social Networking Site use-effects on mental health and the brain - Weinstein, Aviv M. (Frontiers in Psychiatry, 2023)
The association between excessive use of Social Networking Sites (SNS) and mental health is raising serious concern among health and education professionals. Problematic SNS use has been associated with an increased rate of depression, anxiety, stress, obsessive-compulsive disorder (OCD), attention-deficit/hyperactivity disorder (ADHD), and propensity to excessive alcohol use. It may also lead to vulnerability to aggression, cyberbullying and fear of missing out (FOMO). There is little evidence for cognitive impairments, but there is some preliminary event-related potentials (ERPs) evidence for inefficiency in allocating and monitoring resources and inhibitory control. Problematic SNS has been associated with the personality traits of conscientiousness agreeableness and neuroticism, and with narcissism. There is evidence for reduced sleep quality and quantity, longer sleeping latency and more sleep disturbance. The few brain imaging studies show some similarity between problematic SNS use and other addictions related to inhibitory-control mechanism, reduced gray matter volumes in the nucleus accumbens, amygdala, and the insula, suggesting rewarding effects of SNS use on the brain. Finally, there is preliminary evidence that treatment with Cognitive Behavior Therapy (CBT) can assist in short-term abstinence intervention to treat problematic SNS use. We conclude that problematic SNS use may have deleterious effects on emotional and social relationships, and more research is required on its effects on cognitive and brain function.